PELATIHAN MICROSOFT WORD UNTUK MENUNJANG PROSES PENDIDIKAN PESANTREN TAHFIZH AL-QUR’AN DAARUL HIKMAH - Sri Rama Putri; Raditia Vindua; Dede Sunandar (Abdi Jurnal Publikasi, 2025)
In the era of globalization where technology, information, and communication (ICT) is developing very rapidly, the world of education is experiencing changes in its management as a result of the demands of utilizing technology. Changes in learning and demands for innovation are important things that must be done. Various applications are available and can be used by educators to develop learning media. The Microsoft Word application is very important to use in this digital era, where Microsoft Word is good for elementary school children to college and even for workers. With the use that is increasingly in demand by several groups both from the office sector and the world of education, for this reason, training was created in the context of community service, which aims to improve the knowledge and understanding of students at the Daarul Hikmah Al-Qur'an Tahfizh Boarding School in using Microsoft Word. This training is expected to be useful for participants to increase their insight and knowledge about the Microsoft Word application. Microsoft Word training is useful for supporting the educational process at the Daarul Hikmah Al-Qur'an Tahfizh Boarding School, which is one of the learning methods that can improve hard skills for students, especially in operating and utilizing Microsoft Word. Currently, the development of information and communication technology plays a very rapid role in helping society. Especially in the Tahfizh Al-Qur'an Daarul Hikmah Islamic Boarding School, this kind of training is something that is very beneficial and useful for male and female students, where in the Islamic boarding school there are no special subjects related to technology, especially computers. With this training, all participants were very enthusiastic to practice directly and hoped that similar training would be held again so that they would understand Microsoft Word in depth. The output of this community service is the publication of scientific articles in the form of national journals..